Fabrication, Validation, and Stability Analysis of Melaleuca alternifolia Oil-in-water Microemulsion for Improved Transdermal Application (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The aim of the study was to develop oil-in-water microemulsion (ME) system for Melaleuca alternifoliafor targeting skin disorders. Materials and Methods: The formulation of ME system was done through the watertitration method, which involved various oils, water, surfactants, and cosurfactants. The existence zones of MEwere determined by constructing ternary phase diagrams, where surfactants and cosurfactants (Smix) were taken indifferent ratios along with different combinations of oil and Smix. Quantitative estimation of tea tree oil (TTO) wasperformed using gas chromatography-mass spectrometry followed by total terpenoid estimation, and thereafter,solubility studies of TTO were performed using various excipients. TTO-ME was fabricated and characterizedusing modern characterization techniques (DLS, transmission electron microscopy, and Fourier transform infrared)along with statistical validation and in vitro drug release assessment. Results and Discussion: The optimizedTTO loaded MEs (TTO ME) showed the particle size range between 32 and 160 nm with poly dispersibility indexof 0.297 and zeta potential of âˆ’3.19 mv with almost spherical morphology. The optimized formulation showedthe sustained release of the therapeutic compound and was found to be stable at room temperature for 1 year,suggesting being a promising formulation against dermal infections. Conclusion: TTO was successfully loadedin thermodynamically stable ME system which enhanced its permeation through the transdermal route. Therefore,a novel drug delivery system was introduced, which can be studied on various in vitro and in vivo models furtherto establish its better therapeutic efficacy for various skin disorders.